2018
DOI: 10.1007/s11356-018-2806-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental quality and well-being level in Turkey

Abstract: The environment is an indispensable dimension of human life and affects important concepts such as health, quality of life, life satisfaction, and well-being. The purpose of this study is to determine the effect of environmental elements such as air quality, forest area, waste services, and noise pollution on the well-being in Turkey. The data of the research were obtained from the well-being index for the Provinces Study prepared by the Turkey Statistical Institute in 2015. A hierarchical multiple regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Contribution to economy decreased after stationarity at 2.80%. Adana became province of outflow emigration with an increase by 13% in 2017-2018(Karakuş, 2019. In the same year, there has been a regime change in Turkey and the Turkish Armed Forces has been involved in the war in Syria.…”
Section: Methods Why Surveyed In January-february 2019mentioning
confidence: 99%
“…Human well-being has long been in the context of objective environment where people live. A historical evidence for indication of livable place comes from Hippocrates (Taşkaya, 2018). The neighbourhood and the city people live in influence well-being (Leyden et al, 2011) for which livability is described as precondition (Veenhoven, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Depression symptoms are signs of emotional disorder, and are affected by family and environmental factors [12][13][14][15][16]. For example, Qianrong et al investigated 139 older couples and found that marital satisfaction of married men could decrease the depression score, suggesting that marital satisfaction was a considerable factor affecting depression in the older population [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bae's research demonstrated that perceived health status and family relationships were the most powerful and key predictors of depressive symptoms among elderly adults [35]. Perceived health status has also been regarded as a mediator of environmental pollution and health [37][38][39]. For example, Fan's study suggested that self-rated health played an important mediation role in the association between environmental pollution and subjective well-being [33].…”
Section: Introductionmentioning
confidence: 99%